-3x+2 = 2x-8 8+2 = 2x+3x 10 = 5x x = 2
(-2, 4)
3x = -12 so x = -4
12 + 3x = 412 - 12 + 3x = 4 - 123x = -83x/3 = -8/3x = -8/3x = -(2 2/3)
x=1
-3x+2 = 2x-8 8+2 = 2x+3x 10 = 5x x = 2
(-2, 4)
3x = -12 so x = -4
x=1.6225
-3x + 6 + 15x =11x + 8 ie -3x + 15x - 11x = 8 - 6 ie x = 2
12 + 3x = 412 - 12 + 3x = 4 - 123x = -83x/3 = -8/3x = -8/3x = -(2 2/3)
x=1
2
y=4x2+3x+8
5x + 8 = 3x + 25x - 3x = 2 - 82x = -6x = -6/2x = -3Check:5(-3) + 8 = 3(-3) + 2-15 + 8 = -9 + 2-7 = -7
-2
If: 3x+8 = 14 Then: 3x = 14-8 So: 3x = 6 Divide both sides by 3: x = 2